Energy Use in Bitcoin Mining : The Environmental Impact of Cryptocurrencies - Jones, Benjamin A.; Goodkind, Andrew L.; Berrens, Robert P. 1962- (Routledge, 2025)
This book provides a unique introduction to Bitcoin mining's energy use and environmental impacts. Bitcoin, the largest and most well-known cryptocurrency, has ignited the world of decentralized finance and digital currencies. However, Bitcoin has a major problem: it uses massive amounts of energy to produce or 'mine' the coins, and this energy use has tremendous environmental consequences. By recent estimates, Bitcoin mining's global electricity use is larger than entire countries such as the Netherlands and Argentina. In this book, the authors explain the process by which Bitcoin is mined, why it requires significant energy, and what we know about where that energy comes from. It also explores the environmental impacts and associated monetary damages of this energy use. Further, the book presents the current state of scientific knowledge around these questions and provides original economic damage estimates from the authors and compares them to those of other goods and services. The book discusses links between Bitcoin and climate change, public health, air pollution, 'e-waste', water, and land use. It concludes by discussing alternative ways in which Bitcoin mining can be made green by using less energy, as well as the policy and regulatory challenges that may hinder progress toward this goal. Innovative and insightful, this book will be of great interest to students, scholars, and industry professionals who are researching and working in the areas of cryptocurrencies, economics, business and finance, engineering, energy, and environmental studies more broadly.
Keywords: Cryptocurrencies -- Environmental aspects.; Bitcoin; proof-of-work; monetary damages; social cost of carbon; Bitcoin mining; energy and environmental impacts; elektronické knihy; electronic books